2006
DOI: 10.1093/humrep/del130
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ICSI with ejaculated spermatozoa in a series of men with distinct ultrastructural flagellar abnormalities

Abstract: The rate of ICSI success may be influenced by the type of flagellar abnormality. ICSI provides a suitable solution for patients with sperm flagellar defects but raises the question of the consequences of a specific (and primary flagellar) abnormality on oocyte fertilization, on embryo and fetal development as well as on live birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 52 publications
2
26
0
5
Order By: Relevance
“…Additional aberrations have included absence of the radial spokes [32], peripheral microtubule defects, dysplasia for the fibrous sheath [12], non-specific axoneme defects [33], complete ciliary aplasia, orientation defects [34], and absence of the central microtubule pair [28,31,35]. Wolff et al also reported a case of immotile cilia syndrome where the axonemes of the spermatozoa tails were complete except they lacked the two central microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Additional aberrations have included absence of the radial spokes [32], peripheral microtubule defects, dysplasia for the fibrous sheath [12], non-specific axoneme defects [33], complete ciliary aplasia, orientation defects [34], and absence of the central microtubule pair [28,31,35]. Wolff et al also reported a case of immotile cilia syndrome where the axonemes of the spermatozoa tails were complete except they lacked the two central microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of uncharacterized immotile sperm makes fertilization after ICSI unpredictable and decreases both fertilization and pregnancy rates. 50,51 When no motile spermatozoa are found in the ejaculate, the patient should produce a second ejaculate. In most patients, the second semen sample often contains a few motile spermatozoa for use with ICSI.…”
Section: Absolute Indications For Icsi In Male Factor Infertilitymentioning
confidence: 99%
“…In the literature, few individual case reports have been published, there were 15 reported cases of DFS/stump tails/short tails [4,13,15]. Bacceti et al, [14] reported a large series of 12 patients with DFS sperm defects while Mitchell et al, [43] investigated ICSI outcomes for 21 patients with distinct ultrastructural flagellar abnormalities, 12 of them presented with "short tail" syndrome. Rawe et al, [19] and Moretti et al, [20] have reported respectively one and two cases of DFS sperm defect associated with acephalic sperm and abnormal head-tail attachment.…”
Section: Discussionmentioning
confidence: 99%
“…The mean overall fertilization rate was 63 %, 10 pregnancies were achieved (83 %), two miscarriages (20 %) and eight deliveries (67 %), and a total of 14 healthy babies born. Mitchell et al, [43] reported ICSI outcomes for 21 patients with distinct ultrastructural flagellar abnormalities, 12 of them presented with "short tail" syndrome . Only for 14 out of 21 patients fertilization was achieved with a mean rate of 62 %, pregnancy rate of 57 % (12 pregnancies), and live-birth rate of 43 % (9 deliveries).…”
Section: Discussionmentioning
confidence: 99%